QUALITY ASSESSMENT OF PATIENTS REFERRAL LETTERS - Yousif, Eisa Mohammed; El Rahman E, Hibat; M. A, El Rayah (Gezira Journal of Health Sciences; Vol 6 No 2 (2010), 2010)
This study is a descriptive undertaking aiming at assessing the quality of referral letters submitted to departments of seven selected Medani Hospitals from different levels of health institutions.   Required data was collected by observation and by a check list with a scoring system. Indirectly relevant data was extracted from historical data sources. METHOD:  The total number of the collected referral letters was 412 of which 206 were randomly and systematically sampled out and studied. The letters were checked for items that should be included in a good referral letter. Results and interpretation were obtained manually and with the aid of SPSS. RESULTS: It was found that 171 (83%) letters were of poor quality. Factors that lead to this were: bad handwriting, writing on slips of paper 69 (33.5%), senders poor perception of the importance of mentioning the negative as well as positive findings, improper utilization of health units pharmacies and laboratory facilities and lastly referring of cases without trying to manage first at the site of origin. Recommendations suggested were: training of GPs and health auxiliaries on writing good referral letters as well as having continuous medical education to improve their knowledge and skills on managing cases before instantly referring them. Design a standardized "fill-in- space" form and provide facilities for typing.